Nilai-Nilai Pendidikan Islam Dalam Pelaksanaan Akikah dan Tasmiah Di Kel.Baamang Hulu Kec.Baamang Kab.Kotim - Muhammad Fitrianur (LP2M IAIN Palangka Raya, 2015)
This research to determine the values contained in the Islamic Education and tasmiah akikah implementation in Ex. Baamang Hulu district. Baamang Kab.Kotim. In this study using qualitative research. The subjects were four (4) people. While informants / respondents in this study is three (3) people consisting of 1 (one) of the Head of Village / Sub, 1 (one) of the religious leaders who were in the area, one (1) person public figure in tuakan, and knowing about the implementation akikah and tasmiah. The results showed that (1) the implementation akikah and tasmiah in Kel.Baamang Hulu Kec.Baamang Kab.Kotim first prepared an animal for a baby shower, then prepare some other tools. Then prepare the equipment for the implementation tasmiah, place the dish, and the baby, after it began the process tasmiah. (2) The educational values of Islam contained in the implementation akikah and tasmiah based on the opinion of 4 subjects (AS, AM, L, USA) and 3 informants (S, MI, AM) can be taken kesmpulan, based on the teachings of Islam